2000
DOI: 10.1128/jb.182.11.3197-3203.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Cloning, and Initial Characterization of rot , a Locus Encoding a Regulator of Virulence Factor Expression in Staphylococcus aureus

Abstract: A chromosomal insertion of transposon Tn917 partially restores the expression of protease and alpha-toxin activities to PM466, a genetically defined agr-null derivative of the wild-type Staphylococcus aureus strain RN6390. In co-transduction experiments, transposon-encoded erythromycin resistance and a protease-and alpha-toxin-positive phenotype are transferred at high frequency from mutant strains to agr-null strains of S. aureus. Southern analysis of chromosomal DNA and sequence analysis of DNA flanking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
192
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(202 citation statements)
references
References 35 publications
7
192
3
Order By: Relevance
“…We found the rot gene to be poorly transcribed in the early (lag) and post-exponential phases of growth, whereas transcription was significantly higher in the exponential phase in the wild-type strain. This finding is consistent with the earlier observation that the rot gene is transcribed maximally in the exponential phase of growth (McNamara et al, 2000). Northern analysis of rot transcription in mutants of agr, sae, sigB and nine sarA family genes revealed that transcription of rot remains unaltered in these mutants at the post-exponential phase of growth, with the exception of sarA and sarS.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…We found the rot gene to be poorly transcribed in the early (lag) and post-exponential phases of growth, whereas transcription was significantly higher in the exponential phase in the wild-type strain. This finding is consistent with the earlier observation that the rot gene is transcribed maximally in the exponential phase of growth (McNamara et al, 2000). Northern analysis of rot transcription in mutants of agr, sae, sigB and nine sarA family genes revealed that transcription of rot remains unaltered in these mutants at the post-exponential phase of growth, with the exception of sarA and sarS.…”
Section: Discussionsupporting
confidence: 81%
“…Although the phenotypic characterization of the rot gene has been performed thoroughly, the regulation and characterization of rot transcription are not well defined (McNamara et al, 2000;McNamara & Bayer, 2005;Said-Salim et al, 2003;Tseng & Stewart, 2005). Therefore, in order to determine the transcriptional start site and the promoter structure of the rot transcript and the probable length of the rot open reading frame, primer extension analysis was performed with total RNA isolated from the wild-type RN6390 and sarA mutant strains (Fig.…”
Section: Characterization Of the Rot Transcriptsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The success of S. aureus as a pathogen lies in its ability to exploit multiple virulence factors regulated by complex network of global gene regulators that includes but not limited to Agr (accessory gene regulator), SarA (staphylococcal accessory regulator), Sae (S. aureus exoprotein expression), SigB (sigma factor B) and Rot (repressor of toxins). [2][3][4]9,16,17 Recently, we reported the differential expression of ssl8 in seven clinically relevant S. aureus isolates and showed that ssl8 expression in the Newman strain is regulated by Sae and Agr. 16 In this brief communication, we show that the ssl8 expression in the common laboratory strain, RN6390 is regulated differently than the Newman strain suggesting ssl8 regulation is strain dependent.…”
Section: Pat Hogenesis Of Staphylococcus Aureus Is Complex Andmentioning
confidence: 99%